Short Term Aging Effect of Asphaltic Concrete Incorporating Charcoal Ash from Coconut Shell - Putra Jaya, Ramadhansyah; K. A., Masri; Haryati, Awang; M. K. I. M., Satar; Mohd Rosli, Hainin; Norhidayah, Abdul Hassan; Muhammad Naqiuddin, Mohd Warid; Haryati, Yaacob; Juraidah, A. (IOP Publishing, 2020)
Numerous studies have been conducted to improve the performance of asphalt mixture properties in comparison with conventional mixes. One of the alternatives is utilizing waste agriculture product as additive or replacement into bitumen mixture. Coconut shell is one of the agricultural wastes that can be utilized. This paper aims to study the effect of asphaltic concrete incorporating charcoal ash from a coconut shell under short term aging condition. Charcoal coconut shell ash (CCSA) was added into a bitumen with 0%, 2%, 4%, 6%, and 8% by weight. The original CCSA was initially ground until getting the particles sizes less than 0.075mm. Laboratory simulation of aging was applied in this investigation. Marshall Stability, volumetric properties, resilient modulus, and dynamic creep test were performed to analyses asphalt mixture containing CCSA. It was observed that the addition of CCSA in asphaltic concrete gives the significant development in stability, modulus of resilient and creep stiffness. This study suggests that 4% and 6% of CBA as a supplementary binder could improve the mechanical properties of asphaltic concrete even under aging conditions.